واقع الاتصال الداخلي في المؤسسة التربوية بثانويات غليزان دراسة ميدانية بثانوية الشهيد تسغات تسرات الحمادنة انوذجا ى - (:unkn) unknown (My University, 2020)
ملخص الدراسة: یعتبر الاتصال عملیة دینامیكیة تعمل على نقل وتبادل المعلومات والأفكار والخبرات بین شخصین أو أكثر.ومن خلال هذه الدراسة تم التطرق إلى الاتصـال الـداخلي فـي المؤسسـة باعتبـاره جانبـا مهمـا ومـؤثرا علـى أداء الموارد البشریة ،واخترنا المؤسسة التربویة كنمـوذج خـاص مـن المؤسسـات باعتبارهـا مـن أهـم المؤسسـات التـي لها مكانة هامة في الحیاة الاجتماعیة ،والتـي تحظـى باهتمـام بـالغ فـي المجتمـع نظـرا لمـا تسـاهم بـه مـن تربیـة وتعلیم وتكوین ،حیث تمحورت إشكالیة هذه الدراسة حول ما هو واقع الاتصال الداخلي في المؤسسات التربویة الجزائریة بغلیزان ؟ وكـان الهـدف الرئیسـي لهـذه الدراسـة هـو معرفة واقع الاتصال في المؤسسة التربویة، والكشف عن نمط الاتصال السائد و أهم الوسائل المستخدمة، التعرف على معوقات الاتصال و مدى نجاحه في تحقیق أهداف المؤسسات التربویة الجزائریة. في حین اعتماد لدراسة هذا الموضوع على خطوات المنهج المسحي الوصفي في إجراء الدراسة المیدانیة ،بعینة من المؤسسة التربویة في دائرة الحمادنة ولایة غلیزان ،بإتباع المسح الشامل على كل الموظفین في هذه المؤسسة التي قدرت بــ 60مفردة ، أما بالنسبة لأدوات جمع البیانات فقد اخترنا استمارة كأداة أولیة و تقنیة المقابلة والملاحظة كأداة ثانویة،لنصل في الأخیر إلى نتائج توضح لنا أن: ـــ الاتصال الداخلي بمثابة شریان المؤسسة الذي یوفر المعلومات اللازمة عبر مختلف القنوات ، الأمر الذي یساهم في اتخاذ قرارات فعالة. -إن نجاح أو فشل أي مؤسسة یقاس بقدر نجاح خطوات وعملیات الاتصال بها، وهذا ما یجعل من الضرورة للمؤسسة أن تتحصل على معلومات ذات الجودة والدقة والمصداقیة.- الاتصال الداخلي في المؤسسة التربویة قائم على الاتصال الرسمي بحكم طبیعة نشاطها ، حیث نجد أن نمط الاتصال السائد في المؤسسة هو الاتصال النازل في شكل تعلیمات وأوامر وقرارات من طرف المسؤول، وكذلك الاتصال الصاعد الذي یكون كرد على التعلیمات والأوامر وقد یكون هذا الاتصال أحیانا في شكل مقترحات ومستجدات بخصوص المهام ولكن أحیانا ما تؤخذ بعین اعتبار المسؤول. أكثر الوسائل الاتصالیة المستخدمة في تبلیغ المعلومات و التعلیمات في المؤسسة هي وسائل الاتصال الشفویة خاصة الاجتماعات. ـــ معظم المشاكل التي تعاني منها ثانویات ولایة غلیزان مشاكل متعلقة بالإدارة. -یساهم الاتصال في تحقیق أهداف المؤسسات التربویة بولایة غلیزان بنسبة كبیرة. الكلمات المفتاحیة :الاتصال ، المؤسسة التربویة.Abstract: Communication is a Dynamics process that works on transfer and exchange information, ideas and experience between two or more. Through this study, I have touched the internal communication inside an institution because of its importance and effect on resource performance. I choose the education institution as a special form because it is the most important institution that have an important status in social life which receives great attention in society, because it contributes with education and training. The problematic of this study revolved around the reality of internal communication in the Algerian education institutions in relizane. The main objective of this study is knowing the reality of communication in educational institution, detecting the prevailing communication style, and the most imported methods used, identify the obstacles to communication and the extent of its success in achieving the goals of the Algerian educational institutions. This study relied on the steps of the descriptive survey approach in conducting a field study with a sample from the educational institution in el hmadna district relizane province by following a comprehensive survey of all employees in this institution which was estimated at 60 individuals. Through this study, I reach this result: Internal communication is the life blood of the institution providing necessary information through various channels which contributes to effective decision _ making. The success and failure of any institution is measured by the success of its steps and processes. The internal communication in the educational institution is based on formal communication the pre dominant communication in the institution is communication comes down in the form of instructions from the administrator.As well as the upward communication which is a response to instructions and orders, and this communication may sometimes be in the form of proposals regarding tasks. The most common means of communication used in communicating in formation and instructions in the institution is the oral means of communication especially meetings.  Most of the problems in high schools in relizane are administrative problems. Communication contributes to achieving the goals of the educational institutions in relizane to a large extent. Key words: communication, educational, institution.
Keywords: الاتصال الداخلي،المؤسسة التربوية،ثانوية غليزان